703. Do Patients with Drug Use-Associated Infective Endocarditis Receive Differential Care?. (31st December 2020) - Ceniceros, Ashley; Felson, Uriel; Fox, Aaron
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) is the preferred modality for long term intravenous antibiotics for infections such as infective endocarditis (IE). People with drug use-associated (DUA) infections achieve similar outcomes as those with non-DUA-infections when treated using OPAT. The study objective was to compare OPAT use between cohorts of patients with DUA-IE and non-DUA-IE. Methods: This retrospective cohort study compared OPAT use for DUA-IE vs. non-DUA-IE in adults hospitalized between 1/1/15 and 9/1/19 at three Bronx, NY hospitals. We used multivariable logistic regression to assess the association between DUA-IE and discharge with OPAT, adjusting for clinically significant covariates that were decided a priori. Additional models excluded patients with unstable housing and those who left against medical advice (AMA). Figure 1: Flow chart of inclusion and exclusion criteria Results: The cohort included 457 patients (346 non-DUA-IE, 111 DUA-IE). Compared to those with non-DUA-IE, DUA-IE patients were younger (mean age 54.9 years), more commonly male (65.8%), Hispanic (44.1%), Medicaid insured (40.5%), and undomiciled (9%). In models adjusting for age, sex, race/ethnicity, insurance, year of admission, length of stay, socioeconomic status, Charlson Comorbidity Index, MICU admissions, and infectious disease consults, DUA-IE patients had significantly lower odds of being discharged with OPAT than non-DUA-IE patients (aOR 0.16, 95% CI 0.08, 0.34). Odds of being discharged with OPAT remained lower for DUA-IE patients after excluding unstably housed patients (aOR 0.17, 95% CI 0.09, 0.38) and patients who left AMA (aOR 0.23, 95% CI 0.11, 0.47). Table 1: Non-DUA-IE and DUA-IE Patient Characteristics Table 2: Unadjusted and Adjusted Odds Ratios for Discharge with OPAT Table 3: Odds Ratios for Discharge with OPAT Among Patients Stably Housed and Retained in Care Conclusion: Patients with DUA-IE were discharged with OPAT significantly less than those with non-DUA-IE, and patients having unstable housing or leaving AMA did not account for these differences. These data do not elucidate whether differential treatment was clinically appropriate, but other studies have demonstrated safety and effectiveness of OPAT in DUA-infections. Understanding whether addressable clinician-related factors, including their attitudes toward people who use drugs, contribute to differential treatment is an important next step in this research. Disclosures: All Authors : No reported disclosures